2002
DOI: 10.1677/joe.0.1750211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiac oxytocin system and natriuretic peptide during rat gestation and postpartum

Abstract: We have recently uncovered the presence of an oxytocin system in the heart and found that oxytocin is a physiological regulator of atrial natriuretic peptide (ANP), a diuretic, natriuretic and vasodilator cardiac hormone. However, dynamic changes in these systems during gestation, when mechanisms of volume and pressure homeostasis are altered, are not clear. Accordingly, ANP, oxytocin and oxytocin receptors were evaluated in rat hearts and plasma at three stages of gestation (7, 14 and 21 days) and at 2 and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…This decrease in cGMP may have resulted from downregulated natriuretic peptides and their GC receptors, as well as upregulated clearance receptors, which act as a buffering system, reducing the effective pool of natriuretic peptides. Decline of LV OTR, eNOS, iNOS and ER , and, as we have reported previously, plasma ANP (Mukaddam-Daher et al 2002) may also contribute to cGMP reduction in the LV. The reduced levels of cGMP at term favor a shift of balance toward enhanced heart work at the onset of labor.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This decrease in cGMP may have resulted from downregulated natriuretic peptides and their GC receptors, as well as upregulated clearance receptors, which act as a buffering system, reducing the effective pool of natriuretic peptides. Decline of LV OTR, eNOS, iNOS and ER , and, as we have reported previously, plasma ANP (Mukaddam-Daher et al 2002) may also contribute to cGMP reduction in the LV. The reduced levels of cGMP at term favor a shift of balance toward enhanced heart work at the onset of labor.…”
Section: Discussionsupporting
confidence: 84%
“…The actions of estrogens and progesterone are mediated by specific binding sites in vascular tissue and in the heart. Their hormonal effects include changes in the synthesis or release of cardiac natriuretic peptides, and in the oxytocin system (Mukaddam-Daher et al 2002, Wang et al 2003 as well as NOS and cGMP regulation (Weiner et al 1994, Linke et al 2002. In addition, direct interaction between these systems may also be involved in pregnancy-associated cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes then were incubated for 2 hr at room temperature with 10% fat-free milk in Tris-buffered saline containing Tween-20 (TBS-T) composed of 20 mM Trizma-base (Sigma), 0.15 M sodium chloride, 0.1% polyoxyethylene-sorbitan monolaurate (Sigma). A well characterized rabbit V 1a receptor antibody (1 g/ml; Chemicon, Temecula, CA) (Hurbin et al, 2002;Clerget-Froidevaux and Pittman, 2003) or OXT receptor antibody (5 g/ml; RDI, Flanders, NJ) (Mukaddam-Daher et al, 2002) were used. After 2 hr of incubation with the primary antibody the membrane was washed with TBS-T and incubated with goat antirabbit IgG conjugated with horseradish peroxidase (1:4000) (Santa Cruz Biotechnology, Santa Cruz, CA) for 1 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…New functions have recently been reported for oxytocin as a positive and negative regulator of cell proliferation in different tissues [3] and a differentiation factor for myoepithelial cells in the mouse mammary gland [4]. Recent studies have indicated the role of oxytocin in cardiac development as the oxytocin receptor increases at the protein level in the murine heart from day 7 of gestation, when cardiac differentiation starts [5]. Furthermore, oxytocin has been found to be a potent inducer of P19 and cardiomyocyte differentiation of adult stem cells [6,7].…”
Section: Introductionmentioning
confidence: 99%